2012
DOI: 10.1002/adv.21274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Strain Rate and Drawing Temperature on the Mechanical Behavior of EVOH and EVOH Composites

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Endotherm curves for blends with the random copolymer were less pronounced and wider as the content of the mixture was increased, in comparison with the curves related to the blends with the heterophasic polypropylene. This behaviour is attributed to a broad range of crystals with different lamellar thickness [31]. As the random content in the blend increases (H-20R), a decrease in the melting point is also observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endotherm curves for blends with the random copolymer were less pronounced and wider as the content of the mixture was increased, in comparison with the curves related to the blends with the heterophasic polypropylene. This behaviour is attributed to a broad range of crystals with different lamellar thickness [31]. As the random content in the blend increases (H-20R), a decrease in the melting point is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…Shoulder at lower temperatures related to the annealing process [14,15,16,17,18] and also associated with the melting of different crystal populations disappears progressively as the annealing temperature increases. It seems that the increment on molecular mobility at higher temperatures promotes the formation of a more dense and stable crystalline form [31]. Membrane thermograms display similar endothermic curves for annealing temperatures above 150 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where ΔH m is the experimental enthalpy of melting and ΔH 0 m ¼ 157.8 J/g is the poly(vinyl alcohol) (PVA) equilibrium enthalpy of melting (theoretical value of the polymer supposed to be 100% crystalline) [39,40]. It is shown that the ethylene segments in the EVOH copolymers with 40-80 mol% of the vinyl alcohol groups crystallize into a monoclinic lattice similar to that of PVA regardless of the ethylene sequences, located as punctual defects in the main crystalline lattice [40].…”
Section: Characterization Techniquesmentioning
confidence: 99%